The efficacy of metformin and clomiphene citrate combination compared with clomiphene citrate alone for ovulation induction in infertile patients with PCOS - Papa Dasari; G K Pranahita (Wolters Kluwer Medknow Publications, 2009)
Context: Low ovulatory and pregnancy rates with clomiphene citrate (CC) in anovulatory polycystic ovarian syndrome (PCOS). Aim: To find out the ovulatory and pregnancy rates in infertile PCOS subjects who receive CC alone and a combination of metformin and CC. Setting and Design: A prospective controlled clinical trial conducted in the outpatient department from August 2003 to August 2005. Materials and Methods: Twenty-four infertile PCOS women received CC alone at incremental doses of 50 mg up to 150 mg for three cycles and then at a dose of 150 mg for another three cycles (control group). The study group (16 PCOS) received the same dose of CC along with 1500mg of metformin. Ovulation was monitored by transvaginal sonography up to six cycles or till pregnancy occurred. Statistical Analysis: This was carried out using software SSPS, version 10. Fisher's exact test was used to calculate the ovulatory rates. Nine subjects of the control group who failed to conceive with CC had opted for CC and metformin and their ovulatory rate was calculated using statistical software, namely SPSS 15.0, Stata 8.0, MedCalc 9.0.1 and Systat 11.0 using Fischer's exact test. Results: The metformin and clomiphene combination resulted in a significantly higher rate of ovulation ( P = 0.0016). The pregnancy rate was 8% with CC and 24% with metformin and CC. The CC failure group also ovulated at a similar rate as that of the study group. Conclusions: The ovulatory rate and the pregnancy rate with the metformin-CC combination was found to be higher when compared with CC alone. Metformin increased the ovulatory rate in CC failures, also implying increased sensitivity to CC.